Information Technologies and Artificial Intelligence in the Training of Future Teachers (Experience of the Department of Music Art at H.S. Skovoroda Kharkiv National Pedagogical University) - Fomin, Volodymyr; Vasilyeva, Oksana; Kim, Oleksandr; Yuryeva, Kateryna (International Scientific Conference “EDUCATION, RESEARCH, PRACTICE” Proceedings, 2024)
The relevance of this research is driven by the need to generalize the unique experience of Ukrainian educators in utilizing information technologies and artificial intelligence in the professional training of future teachers in artistic disciplines: music and the integrated course "Art". The aim of this research is to outline and summarize the main technological solutions used by the faculty of the Department of Music Art in conducting choral classes, choral conducting, and teaching methodology of the integrated course "Art", among others. The research methodology primarily involved the analysis and generalization of personal experience, observation during classes, surveys of students and colleagues, and more. The results demonstrated the presence of a unique experience in Ukraine, and possibly beyond, in using information technologies in areas previously considered least adaptable for this purpose: working with choirs, teaching choral conducting and vocals, and even preparing and conducting the qualifying exam in choral conducting and preparation for event-art activities in a remote format. The conclusions outline the prospects for further research, which will detail the pedagogical technologies developed by the faculty of the Department of Music Art at H.S. Skovoroda Kharkiv National Pedagogical University and compare them with similar international experiences.